Kepemimpinan KH Sahal Mahfudh di Lembaga Pendidikan Islam: Analisis SWOT - Ahmad Muchlishon (Journal of Islamic Education, 2026)
This study aims to analyze the educational leadership patterns of KH MA Sahal Mahfudh (Kiai Sahal) at three Islamic institutions: Pesantren Maslakul Huda (PMH) Kajen, Pati, Perguruan Islam Mathali’ul Falah (PIM) Kajen, Pati,, and Universitas Nahdlatul Ulama (UNISNU) Jepara. The research uses a qualitative method, combining library research with field research through interviews and observations. Data were analyzed using the SWOT (Strengths, Weaknesses, Opportunities, Threats) framework with historical and sociological approaches. The results show that Kiai Sahal implemented a collective-participatory-transformational leadership style, breaking the tradition of centralized kiai authority by delegating power to subordinates. Crucial policies include the formation of the Pesantren-Owned Business Entity (BUMP) for financial independence at PMH, the consistency of the "Independent Curriculum" at PIM which rejects national standardization to maintain religious depth,The study concludes that Kiai Sahal’s leadership is an effective prototype for modernizing Islamic education, successfully integrating religious excellence (akram) and social competence (shalih) to ensure institutional resilience and relevance in the global era